PENYELESAIAN MASALAH LINTASAN TERPENDEK FUZZY DENGAN MENGGUNAKAN ALGORITMA CHUANG – KUNG DAN ALGORITMA FLOYD - Anik Musfiroh; Lucia Ratnasari (MATEMATIKA FSM, UNDIP, 2012)
Abstract : In the classic graph, shortest path problem is related problem with determination of the which are connected in a graph that form the shortest distance between source node and the destination node. This idea is extended to solve the fuzzy shortest path problem. In this paper, will be discussed about Chuang - Kung algorithm and Floyd algorithm to solve shortest path problem. Chuang - Kung algorithm’s steps is to determine all pass possible path from source node to destination node, then compute value of similarity degree SLmin, Li with Lmin is the fuzzy shortest length and Li is length of possible path. While for Floyd algorithm, the first step is to determine the initial distance matrix D0 and the matrix of the initial order S0 , then check this elements. If in matrix Dk element is dik+dkj<dij so dij replaced with Lmin dij, dik+dkj . Then replace elements matrix Sk with k . Changes sij in matrix Sk following to changes dij on matrix Dk .